AB0718 Cardiac Tamponade and Severe Pericardial Effusion in Systemic Sclerosis. (9th June 2015) - Iniesta, N.; Fernández-Morales, A.; Fernández-Codina, A.; Hurtado, R.; Simeόn-Aznar, C.P.; Fonollosa, V.; Cervera, R.; Espinosa, G.
Abstract : Background: Pericardial effusion is common in patients with systemic sclerosis (SSc) but often mild and asymptomatic. Cardiac tamponade or severe pericardial effusion are very rare but they can be the first manifestation of the disease preceding skin involvement and have been associated with poor prognosis. Objectives: To describe the clinical characteristics, treatment and outcome of patients with systemic sclerosis (SSc) developing severe pericardial effusion or cardiac tamponade. Methods: SSc patients with severe pericardial effusion or cardiac tamponade from three Spanish hospitals are collected. In addition, a computer-assisted (PubMed, MEDLINE) search of the literature to identify all cases of cardiac tamponade or severe pericardial effusion associated with SSc reported in English, French, and Spanish from 1987 through June 2014 was performed. Patients with other associated autoimmune diseases that could be responsible for the pericardial disease or with other possible causes of pericardial effusion such as non-treated hypo or hyperthyroidism, infections, neoplasm or severe pulmonary hypertension were excluded. Results: We included 40 patients (9 cases from the Spanish hospitals and 31 cases from the literature review). Most of patients (82.5%) were female with a mean age at onset of the SSc of 43.4±14.6 years (range: 15-80 years) and at pericardial involvement of 49.3±15.2 years (range: 18-80 years). 22 (55%) patients had the diffuse cutaneous subtype. 24 (60%) patients presented with cardiac tamponade and the remaining 16 (40%) as severe or massive pericardial effusion. Pericardial involvement was previous or simultaneous to SSc diagnosis in 13 (32.5%) cases. In most of cases (88.9%) pericardial fluid analysis disclosed an exudate. Half of patients received steroids and 35% needed surgical treatment. Five (12.5%) patients died due to cardiac tamponade, 3 of them during the acute phase and the remaining two, 2 and 9 months later, respectively. Fourteen out of 32 (43.8%) patients presented a relapse of pericardial effusion with a median follow-up of 8.5 months. Conclusions: Although cardiac tamponade or severe pericardial effusion is an infrequent complication in SSc patients, it can be the first manifestation of disease associated to the diffuse cutaneous subset. No specific treatment for this complication is known. Conclusions: Although cardiac tamponade or severe pericardial effusion is an infrequent complication in SSc patients, it can be the first manifestation of disease associated to the diffuse cutaneous subset. No specific treatment for this complication is known. References: Desai CS, Lee DC, Shah SJ. Systemic sclerosis and the heart: current diagnosis and management. Curr Op Rheumatol 2011; 23: 545-54. Thompson AE, Pope JE. A study of the frequency of pericardial and pleural effusions in scleroderma. Br J Rheumatol 1998;37:1320-3. Perez-Bocanegra C, Fonollosa V, Simeon CP, Candell J, Solans R, Gomez A, Vilardell M.Pericardial tamponade preceding cutaneous involvement in systemic sclerosis. Ann Rheum Dis 1995;54:87-8. D'Angelo WA, Fries JF, Masi AT, Shulman LE. Pathologic observations in systemic sclerosis (scleroderma). A study of fifty-eight autopsy cases and fifty-eight matched controls. Am J Med 1969;46:428-40. Disclosure of Interest: None declared